Identification of differentially expressed proteins and phosphorylated proteins in rice seedlings in response to strigolactone treatment. - Fangyu Chen; Liangrong Jiang; Jingsheng Zheng; Rongyu Huang; Houcong Wang; Zonglie Hong; Yumin Huang (PLoS ONE, 2014)
Strigolactones (SLs) are recently identified plant hormones that inhibit shoot branching and control various aspects of plant growth, development and interaction with parasites. Previous studies have shown that plant D10 protein is a carotenoid cleavage dioxygenase that functions in SL biosynthesis. In this work, we used an allelic SL-deficient d10 mutant XJC of rice (Oryza sativa L. spp. indica) to investigate proteins that were responsive to SL treatment. When grown in darkness, d10 mutant seedlings exhibited elongated mesocotyl that could be rescued by exogenous application of SLs. Soluble protein extracts were prepared from d10 mutant seedlings grown in darkness in the presence of GR24, a synthetic SL analog. Soluble proteins were separated on two-dimensional gels and subjected to proteomic analysis. Proteins that were expressed differentially and phosphoproteins whose phosphorylation status changed in response to GR24 treatment were identified. Eight proteins were found to be induced or down-regulated by GR24, and a different set of 8 phosphoproteins were shown to change their phosphorylation intensities in the dark-grown d10 seedlings in response to GR24 treatment. Analysis of these proteins revealed that they are important enzymes of the carbohydrate and amino acid metabolic pathways and key components of the cellular energy generation machinery. These proteins may represent potential targets of the SL signaling pathway. This study provides new insight into the complex and negative regulatory mechanism by which SLs control shoot branching and plant development.